Medial Patellofemoral Reconstruction with a Hamstring Allograft and Proximal Trochlear Bumpectomy - Yining Lu; Nicholas Lemme; Jay S. Amin; Cade C. Smelley; Zachary R. Oppenheim; Adam B. Yanke (Video Journal of Sports Medicine, 2026)
Background: Patellar instability is a common condition in adolescents and young adults, often associated with trochlear dysplasia, patella alta, and increased tibial tubercle-trochlear groove distance. While medial patellofemoral ligament (MPFL) reconstruction (MPFLR) is the most common surgical intervention for recurrent instability, patients with high-grade dysplasia and supratrochlear spurs may require adjunctive procedures to restore stability. Indications: Recurrent lateral patellar instability for MPFLR and Dejour type B or D trochlear dysplasia with a trochlear bump height of ≥5 mm and a positive jumping J-sign on physical examination for adjunct bumpectomy. Technique Description: MPFLR using a hamstring allograft, combined with a proximal trochlear bumpectomy, is demonstrated. A superomedial patellar incision was made, and fixation was achieved using 2 knotless PEEK anchors, with a patellar trough created. The Schöttle point was identified fluoroscopically for femoral tunnel placement. The proximal trochlear prominence was resected arthroscopically using a scalpel and a bur under fluoroscopic guidance. The graft was tensioned and fixed with an interference screw, with stability confirmed throughout a full range of motion. Results: MPFLR with hamstring allograft is successful for the majority of patients, with low rates of recurrent instability, apprehension, and reoperation reported in the literature. Proximal trochlear bumpectomy has been described as an alternative to trochleoplasty in cases of high-grade dysplasia with a prominent trochlear spur, with early data suggesting lower recurrence rates and comparable functional outcomes. Discussion/Conclusion: MPFLR with allograft combined with proximal trochlear bumpectomy is a viable technique for patients with recurrent patellofemoral instability and a prominent trochlear spur. Further long-term studies are warranted to establish durability and comparative efficacy. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.